Progress in understanding how clock genes regulate aging and associated metabolic processes - Su, Yanhong; Wang, Meng; Chen, Juan; Bao, Yanan; Wen, Ruikang; Ren, Hui-Wen; Luan, Zhi-Lin (Frontiers in Physiology, 2025)
The circadian system, primarily governed by the suprachiasmatic nucleus of the hypothalamus, consists of a central clock and peripheral clocks distributed across various body tissues. Clock genes generate a 24-h oscillatory cycle via a transcription-translation feedback loop (TTFL). Emerging evidence has identified circadian rhythm disruption as a significant contributor to the risk of metabolic disorders. With aging, the function of circadian rhythms declines, leading to metabolic dysfunction in multiple organs. This article reviews the molecular mechanisms underlying circadian rhythm disruption during aging, with a focus on telomere homeostasis, SIRT1-mediated epigenetic regulation, and the NAD+ metabolic pathway, and systematically analyzes the characteristics of rhythm imbalance in different metabolic organs. A comprehensive understanding of the correlation between circadian rhythms and aging is essential for developing strategies to combat aging and metabolic diseases.